The characteristics of differentiated yeast subpopulations depend on their lifestyle and available nutrients - Čáp, Michal; Palková, Zdena (Scientific reports, 2024)
Yeast populations can undergo diversification during their growth and ageing, leading to the formation of different cell-types. Differentiation into two major subpopulations, differing in cell size and density and exhibiting distinct physiological and metabolic properties, was described in planktonic liquid cultures and in populations of colonies growing on semisolid surfaces. Here, we compare stress resistance, metabolism and expression of marker genes in seven differentiated cell subpopulations emerging during cultivation in liquid fermentative or respiratory media and during colony development on the same type of solid media. The results show that the more-dense cell subpopulations are more stress resistant than the less-dense subpopulations under all cultivation conditions tested. On the other hand, respiratory capacity, enzymatic activities and marker gene expression differed more between subpopulations. These characteristics are more influenced by the lifestyle of the population (colony vs. planktonic cultivation) and the medium composition. Only in the population growing in liquid respiratory medium, two subpopulations do not form as in the other conditions tested, but all cells exhibit a range of characteristics of the more-dense subpopulations. This suggests that signals for cell differentiation may be triggered by prior metabolic reprogramming or by an unknown signal from the structured environment in the colony.
Keywords: Saccharomyces cerevisiae; Cell Differentiation; buněčná diferenciace; sušené kvasnice; fermentace; Fermentation; Yeast, Dried